Sistem Pengukur Suhu Simultan untuk Aplikasi Pemantauan Suhu Tubuh Pasien di Rumah Sakit - Sutisna, Sutisna; Misto, Misto; Hardianto, Hardianto (Lambung Mangkurat University Press, 2010)
An electronic monitoring system has been created for monitoringpatients condition simultaneously. The temperature was converted to the voltageby a temperature sensor consisting of an NTC (negative temperature coefficient)thermistor and the additional circuit that its output voltage change following thechange of thermistor resistance. The number of temperature sensor circuit isused as much as ten. The coverage of temperature measurements were in therange 35oC to 41oC. The main control system was done by Labjack UE9 workingbased program that created in LabVIEW 8.0 software. The result showed that thesystem works well, seen from the accuracy value reached more than 99%(discrepancy (D) less than 0.6%) and precision levels obtained from three timesretrieval of data also amounts to more than 99% (relative uncertainty (I) less than0.6%).